Manufacturing Mini Biopories With Organic Waste Using Used Goods - Febila Rindu Bestari (Abdimas Paspama, 2024)
Waste is classified as environmentally friendly because it can be broken down naturally and is quickly broken down by bacteria. The advantage of organic waste is to increase soil fertility because the organic material is broken down by bacteria and provides excellent nutrients for plant growth. The soil becomes more fertile and the trees grow better. The impact that rubbish has on the lives of the people around us, namely when we walk past a pile of very smelly rubbish on the side of the road, we become anxious and pinch our noses, the rubbish even has an impact on our health. Causes health problems and disease attacks in humans such as diarrhea, dysentery, scabies and fungi. Therefore, a good attitude is needed from every human being to carry out management as well as possible. Waste management through biopore absorption eliminates the need for waste containers in every resident's home, eliminating waste and making society more effective and efficient.